An Organizational Culture and Its Relationship to the Job Performance of the workers - Applied Study on the Public for Telecommunications Corporation in Sana'a - Al-Hamdani, AbdulHadi Hussain (Journal of Economic, Administrative and Legal Sciences, 2023)
The current study aimed to identify the level of values of the prevailing organizational culture and its relationship to organizational performance in the Public Telecommunications Corporation in Sana'a, and to identify the extent to which the values of organizational culture and levels of organizational performance differ according to some personal characteristics (Educational qualification, job grade, number of years of service), the descriptive analytical method was relied upon, applying a two-part questionnaire; The first part is related to the values of organizational culture, the number of its paragraphs is (33) paragraphs. The second part was devoted to measuring the institution's organizational performance level. The number of paragraphs reached (15) paragraphs. The study was applied to a sample of workers in the Public Telecommunications Corporation in Sana'a, which consisted of (107) male and female workers. The results of the study were: that the general average of the prevailing organizational culture in the Public Telecommunications Corporation in Sana'a, It reached (52.3) and standard deviation (767.0) at a high level, and it was found that there are no statistically significant differences between the average organizational culture. Depending on the different personal characteristics (educational qualification, job grade, years of service), it was found that there is a positive (direct) and strong statistically significant correlation at the (01.0) level between organizational culture and organizational performance, while there were found differences according to the years of service variable, in favor of the experience from 5 years to 15 years.
Keywords: Organizational Culture; Job Performance; Public Telecommunications Corporation